Hubungan Kedisiplinan dengan Kemandirian dalam Pembelajaran Pendidikan Agama Islam pada Siswa di SMAN 1 X Koto Kabupaten Tanah Datar - Nisa Angraini Harahap; Januar (YASIN, 2026)
Discipline and learning independence are important aspects of Islamic Religious Education because they contribute to character development and improvement in the quality of students’ learning processes. Although the relationship between discipline and learning outcomes has been widely examined, studies specifically analyzing the relationship between discipline and learning independence in Islamic Religious Education at the senior high school level remain limited. This study aimed to analyze the relationship between discipline and learning independence in Islamic Religious Education among students at SMA Negeri 1 X Koto, Tanah Datar Regency. The study employed a quantitative approach with a correlational survey design involving 92 students selected through simple random sampling. Data were collected using questionnaires and documentation and were subsequently analyzed using descriptive statistics, prerequisite tests, and the Pearson product–moment correlation test. The results indicated a positive and significant relationship between discipline and learning independence in Islamic Religious Education, with a correlation coefficient of 0.442 and a significance value of 0.016. These findings strengthen the literature on character education by demonstrating that discipline plays a role in developing students’ learning independence. This study concludes that improved discipline contributes to the development of learning independence. Theoretically, this study enriches the literature on Islamic Religious Education and character education, while practically, its findings can serve as a basis for schools and teachers to design learning activities that strengthen students’ discipline and independence. Future studies are recommended to involve respondents from a broader population and examine other variables associated with learning independence.